Implementasi Akhlak : Akhlak Pendidik dan Peserta Didik, Akhlak Berbangsa dan Bernegara - M. Agil Febrian; Pangulu Abdul Karim (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
This research aims to analyze the role and impact of the morals of educators and students in shaping the morals of the nation and state. The research method used is library research, with a focus on analyzing scientific literature, books and other reliable sources. The aim of the research is to identify key akhlakvalues ​​in the character of educators and students, as well as analyze their contribution to national and state morals. The research results show that the morals of educators have a central role in shaping the character of students, while the integration of akhlakvalues ​​in the context of national and state life has a positive impact on the formation of a civilized society. This research provides an in-depth understanding of the close relationship between the morals of educators and students and the morals of the nation and state. The implications of these findings can be used as a basis for developing effective character education strategies in forming a generation with character, morals and national identity.